2015
DOI: 10.3168/jds.2014-8414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulla forage (Sulla coronarium L.) on the oxidative status and milk polyphenol content in goats

Abstract: Twelve milking Girgentana goats were allocated into 3 groups and fed 3 diets ad libitum in a 3 × 3 Latin square design with 3 periods. The diets were Sulla fresh forage ad libitum (SUL), Sulla fresh forage ad libitum and 800 g/d of barley meal (SULB), and mixed hay ad libitum and 800 g/d of barley meal (HB). Changes were observed in total polyphenol intake, plasma oxidative status, plasma polyphenol content, metabolic status, milk polyphenol content, and total antioxidant capacity. The fresh forage diets (SUL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 50 publications
3
62
1
Order By: Relevance
“…Previous results also evidenced positive effects of grazing sulla forage on ewe milk production (Sulas et al, 1995;Di Grigioli et al, 2012) and the complementary grazing of sulla resulted useful for improving the nutrition and performance of sheep basically fed on grassland (Molle et al, 2008). Moreover, the milk of condensed tannin exposed ewes grazing sulla at flowering was high in beneficial ω3 fatty acids ) and other results confirm that sulla fresh forage exerts an antioxidant activity (Di Trana et al, 2015). The high nutritive value of sulla forage and its beneficial level of condensed tannins are reported to be associated to bloat save, faster growth rates in young sheep, increased protein use efficiency of rumen, and decreased gastrointestinal parasite infection, nitrogen restitution and methane production in ruminants (Woodward et al, 2002;Ramirez-Restrepo and Barry, 2005;Molle et al, 2009).…”
Section: Implications and Potential Benefits For The Farming System Amentioning
confidence: 57%
“…Previous results also evidenced positive effects of grazing sulla forage on ewe milk production (Sulas et al, 1995;Di Grigioli et al, 2012) and the complementary grazing of sulla resulted useful for improving the nutrition and performance of sheep basically fed on grassland (Molle et al, 2008). Moreover, the milk of condensed tannin exposed ewes grazing sulla at flowering was high in beneficial ω3 fatty acids ) and other results confirm that sulla fresh forage exerts an antioxidant activity (Di Trana et al, 2015). The high nutritive value of sulla forage and its beneficial level of condensed tannins are reported to be associated to bloat save, faster growth rates in young sheep, increased protein use efficiency of rumen, and decreased gastrointestinal parasite infection, nitrogen restitution and methane production in ruminants (Woodward et al, 2002;Ramirez-Restrepo and Barry, 2005;Molle et al, 2009).…”
Section: Implications and Potential Benefits For The Farming System Amentioning
confidence: 57%
“…In ruminants, a relationship between oxidative stress, chronic diseases and physiological stage (Celi, 2011) and a link between energy balance, metabolism, diet and oxidant/antioxidant balance are evidenced (Celi and Gabai, 2015). Moreover, it was found that in those animals dietary antioxidant components may play a pivotal role in blood redox homeostasis and affect production traits (Gatellier et al, 2004;Di Trana et al, 2015). Table 2; * , ** -indicate a statistic significance for P < 0.05 and P < 0.001, respectively Anyway, in contrast to human medicine, the lack of reference values for OS biomarkers in veterinary science makes it difficult to determine whether and when animals are experiencing OS.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies on OS are relatively new in veterinary medicine, in numerous papers OS involvement in several physiological and pathological conditions in livestock is highlighted (Lykkesfeldt and Svendsen, 2007;Celi, 2011). However, it is important to take into account the fact that OS indicators are also influenced by nutrition, and so the nutritional strategy can play a significant role in controlling the oxidant/ antioxidant status in ruminants (Gatellier et al, 2004;Celi et al, 2010;Di Trana et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exposure of ewes (Cabiddu et al, 2005 and2009) and goats (Bonanno et al, 2013b) to the CT contained in sulla forage increased the polyunsaturated fatty acid (PUFA) content in milk, which has beneficial effects on human health as CT inhibits the complete ruminal biohydrogenation of dietary PUFA. In addition, due to its CT content, sulla fresh forage-based diets were able to improve the plasma oxidative status and increase the polyphenol content and total antioxidant capacity of milk in goats (Di Trana et al, 2015).…”
Section: Introductionmentioning
confidence: 99%